Colposcopic evaluation and papanicolaou smear in high risk groups and its correlation with histology - S., Sharanya; M., Shahnas; ., Umadevi; Vahab, Abdul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Cervical cancer is one of the most common gynaecologic neoplasms. PAP smear and colposcopy are used for its early detection. This study aims to find the correlation of colposcopic evaluation with Pap smear in cervical cancer screening and with histology. Methods: All women attending the OPD with unhealthy cervix and abnormal symptoms, who gave written informed consent were included in the study. Pap smear cytological grading, colposcopic findings were recorded. Pap smear and colposcopy findings was compared with histopathology. Results: The study included 73 patients. Pap smear was negative in more than half of the patients (56.2%), followed by atypical squamous cells of undetermined significance in 12 (16.4%), low-grade squamous intraepithelial lesion in 17 (23.3%), high-grade squamous intraepithelial lesion in 2 (2.7%) and squamous cell carcinoma in 1 patient (1.4%). The histopathology showed normal findings in 46 patients (63%), followed by CIN 1 in 11 (15.1%), CIN 2 in 6 patients (8.2%), CIN 3 and squamous cell carcinoma in 5 patients each (6.8%). Pap smear’s predictability of cervical malignancy showed that it had a sensitivity of 48.15, it’s specificity for identifying patients without cervical malignancy was 84.78%. Colposcopy’s predictability of cervical malignancy showed that it had a sensitivity of 88.89%, it’s specificity for identifying patients without cervical malignancy was 95.65%. Conclusions: Colposcopy does seem to be better than Pap smear in diagnosing cervical carcinoma and also identifying patients without it.